On numerical integration for effective stress assessment at notches - Enrico Maggiolini; Paolo Livieri; Roberto Tovo (Fracture and Structural Integrity, 2013)
This paper presents a numerical method for non-local stress assessment by means of a general FE tool and the local stress field. Unlike usual calculations by means of a numerical PDE solver, a more general numerical integration is used. Different solutions are compared theoretically and numerically by evaluating the results obtained by two different FEM commercial software. The application of the non-local tension field is applied to the strength assessment of notches, welded joints and cracks.